Transparansi Dana Kampanye Politik Dalam Menjamin Kepercayaan Publik: Studi Kasus Pemilu 2024 - Yahya, Azka Alycia; Silvana Putri Priageng; Lia Wulandari (Triwikrama: Jurnal Ilmu Sosial, 2025)
This study aims to explore and analyze the transparency of political campaign funds in Indonesia in ensuring public trust through the 2024 election case. Meanwhile, this study uses a qualitative descriptive method. The focus of this study is to understand the relationship between the transparency of political campaign funds in Indonesia and its influence in ensuring public trust. The results of this study are that Indonesia has a campaign fund transparency process that is regulated through regulations and policies aimed at avoiding campaign fund incentives. This transparency certainly affects the guarantee of public trust that is formed because transparency encourages an honest and transparent election process. Even though there is transparency of campaign funds, the election process in Indonesia still encounters obstacles. These obstacles are the lack of transparency of campaign funds which of course also affect public trust in the election process.